FRAGMENTASI LAHAN DAN TINGKAT KESEJAHTERAAN PETANI BAWANG MERAH: SEBUAH ANALISIS REVIEW - Sri Umyati; Sri Ayu Andayani; Itang Ismannudin (JSEP (Journal of Social and Agricultural Economics), 2022)
One of the reasons for the shrinkage of agricultural land in Indonesia is the existence of a system for inheritance and conversion of agricultural land which generally occurs on productive lands. If this condition continues, it will certainly become a serious threat to national food availability. This study aims to determine the extent of land fragmentation that occurs and measure the level of welfare of shallot farmers. The research method used is the descriptive qualitative method with the technique of determining respondents using snowball sampling. The analytical technique used is a descriptive approach and uses welfare indicators from the National Population and Family Planning Agency (BKKBN). Based on the results of the study, land fragmentation in shallot farmers occurs through a system of inheritance, buying and selling, and land renting. Land fragmentation through inheritance is the most common and the largest area of inherited land comes from the wife's family with an average land area of 1.19. The highest level of welfare of shallot farmers was obtained at the prosperous family stage I with a percentage of 37.04%, for the pre-prosperous family stage with a percentage of 33.33%, and the lowest results were obtained at the prosperous family stage with a percentage of 29, 63%.